POLA ASUH REMAJA OLEH ORANG TUA LONG DISTANCE MARRIAGE (Studi terhadap 6 Keluarga di Kelurahan Korong Gadang, Kecamatan Kuranji, Kota Padang) - Mahdil, Annisa; Fachrina; Mira Elfina (Jurnal Administrasi Publik dan Pemerintahan, 2025)
Long Distance Marriage (LDM) refers to a situation where married couples do not live together for certain periods of time and distance. Parents in a long-distance marriage must implement the best parenting practices for their child's growth and development using appropriate methods. This study aims to describe the implementation of parenting and parenting styles by parents in a long-distance marriage and to describe the challenges of parenting faced by parents in a long-distance marriage. This research employs a qualitative method with data collection techniques through observation and in-depth interviews. Informants were selected through purposive sampling, totaling 15 individuals. The informants were divided into two categories: 6 active participants, which parents with children, and 9 observers, including teenegers, extended family, and neighbors. The theories used in this study include parenting theory and types of parenting styles. The results indicate that parenting styles vary among families. Of the six families studied, two employed authoritarian parenting, three utilized democratic parenting, and one adopted permissive parenting. The obstacles faced by each family in a long-distance marriage included limited communication, limited energy, limited physical interaction, and double burden.